2016
DOI: 10.14740/jocmr2435w
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium septicumAortitis of the Infrarenal Abdominal Aorta

Abstract: Clostridium septicum aortitis is a rare infection that has a strong association with occult colonic malignancy. There is also emerging evidence to support the combination of medical and surgical management over medical management alone. To the best of our knowledge, we report the 40th known case of C. septicum aortitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…A recent literature review of clostridial mycotic aneurysms found that combined surgical and medical management (8.4% mortality rate) was far superior to medical management alone with antibiotics (80% mortality rate), with early surgical intervention recommended. 34 The development of a symptomatic prosthetic joint infection, triggering investigation, appears to have facilitated early diagnosis of infective aortitis in our patient. However, several cases of C. septicum infective aortitis described in the literature either died before getting an accurate diagnosis or did not survive to surgical intervention (Table 1).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A recent literature review of clostridial mycotic aneurysms found that combined surgical and medical management (8.4% mortality rate) was far superior to medical management alone with antibiotics (80% mortality rate), with early surgical intervention recommended. 34 The development of a symptomatic prosthetic joint infection, triggering investigation, appears to have facilitated early diagnosis of infective aortitis in our patient. However, several cases of C. septicum infective aortitis described in the literature either died before getting an accurate diagnosis or did not survive to surgical intervention (Table 1).…”
Section: Discussionmentioning
confidence: 82%
“…However, several cases of C. septicum infective aortitis described in the literature either died before getting an accurate diagnosis or did not survive to surgical intervention (Table 1). 34,59 In the presence of C. septicum bacteraemia, early investigation for occult aortitis is therefore recommended; initial presenting symptoms can be vague and non-specific, whilst disease progression to severe sepsis, aneurysmal transformation and vascular catastrophe can occur rapidly (Table 1). 58 Although absent within our patient, synchronous colorectal cancer has been found in 39 of the 56 previously described cases of C. septicum infective aortitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were several reports of C. septicum-infected aortitis, associated with high mortality up to 80% [4][5][6]. According to them, the sites of aortitis included ascending/ arch (n = 15), descending (n = 6), thoracoabdominal (n = 6), and abdominal (n = 20).…”
Section: Discussionmentioning
confidence: 99%
“…Among 15 patients with C. septicum-infected ascending aorta/arch aortitis, as in our case, 5 died with diagnosis of aortitis at autopsy, 3 underwent colon surgery but not aortic surgery (all died), 3 underwent vascular surgery but not cancer surgery (1 died and 2 survived), and 4 underwent aortic surgery followed by colon surgery, as in our case, all of whom survived. All survived patients underwent in-situ grafting, neither axillobifemoral bypass nor endovascular repair [4][5][6]. No patients underwent cancer surgery followed by aortic surgery.…”
Section: Discussionmentioning
confidence: 99%